OPTIMASI FORMULASI KERUPUK PANGSIT KAYA SERAT DAN ANTIOKSIDAN DARI TEPUNG KULIT KAKAO - Satria Bhirawa Anoraga; Cristyn Salle Bayu; Luari Giri Pramelini; Fatma Nurul Hida; Annie Mufyda Rahmatika; Anjar Ruspita Sari (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Cocoa pod husk (CPH) is the main by-product of cocoa processing, which is rich in fiber and antioxidants. Most cocoa husk waste is generally still used as fertilizer and animal feed. Some studies tried to process cocoa pod husk into flour as a functional ingredient. One of the healthy snacks that most people like is dumpling crackers. This study aimed to determine the optimal formulation to produce dumpling crackers as a functional food. The material used in this research is cocoa pod husk from local farmers in Banjaroya village, Kalibawang, Kulonprogo, D.I. Yogyakarta. The research was conducted at the Agroindustrial Product Engineering Laboratory, Agroindustry Product Development Study Program, Vocational School, Gadjah Mada University in June 2022. The ingredients for making dumpling crackers are wheat flour and cocoa husk flour. Parameters observed included crispness, crude fiber content, and antioxidant activity. Optimization was conducted using two factors, X1 (cocoa pod husk flour) and X2 (wheat flour). Three levels of CPH flour (0, 2, and 4g) and wheat flour (10, 20, and 330g) were used for the experiment. Data collection was carried out in three replications, and the experimental value was expressed as mean ± standard deviation (SD). In addition, central composite design (CCD), analysis of variance (ANOVA), and optimization were carried out using Minitab 16 with a 95% confidence level for each response variable. The results showed that adding CPH powder to the dumping cracker formulation did not affect the level of crispness and antioxidant activity but significantly affected the fiber content. At the best formulation of 4g cocoa pod husk flour and 23,131g wheat flour, the crispness was 3,314, crude fiber content was 2,87%, and antioxidant activity was 61,2269, with a composite desirability value was 0,8597. It can be said that the addition of cocoa pod husk powder in the formulation of dumpling crackers can increase the fiber content of the product.